Experiences in affective-sexual obesity contexts - Pereira, Filomena (2017)
The adverse effects of obesity are well documented; however, a growing topic is that relationship with sexuality. Studies show that obesity is associated with a decrease in sexual desire and involvement, avoidance of sexual encounters difficulties in sexual performance, reduced number of sexual partners, and the females to report poor quality of sexual life. Methods: With the objective to find relationships between the level of Body Mass Index (BMI) and sexual experiences, we proceeded to a quantitative descriptive methodology through the BMI calculation to a sample of 306 users of Obesity Therapy (30.7% gender male and 69.3% female) aged 18 and 65 years. Results: The results are Grade I obesity in most (96 to 31.4%) and pre-obesity in 23.5% (72) of respondents, but obesity and pre-obesity, particularly Obesity Grade I (63- 65.6% of individuais) is more prevalent in marital status ' 'Married''. Respondents with higher BMI have lower qualifications. Regarding the number of sexual partners, it appears that the higher the BMI, the lower the number of sexual partners that the sample states: 63 of respondents Obesity Grade I self reports a sexual partner, and the normal weight respondents, this number varies between l and 20, while the class III obesity varies from l to 4 partners. Individuais with normal weight and pre-obesity present frequency of sexual relations / week between 2/3 times / week, while individuais with Obesity Grade II and Grade III have this frequency 1/2 times/week. Conclusion: BMI assumes influence of variable outlines the quality of afiective and sexual experiences. It is considered urgent and relevant to invest in Sexual Education and Nutrition at the level of these populations.